2020
DOI: 10.18050/ucv-scientia.v11i1.2400
|View full text |Cite
|
Sign up to set email alerts
|

Vacas pastoreadas a estaca y su efecto sobre el consumo y condición de la pastura.

Abstract: La investigación se realizó en Celendín - Cajamarca, a 2893 msnm, con el objetivo de determinar el efecto del pastoreo de vacas lecheras a estaca sobre el consumo (Kg MS) y condición de la pastura raigrás-trébol blanco, durante la época de lluvia. La muestra poblacional para determinar el consumo estuvo conformada por 117 vacas de raza Holstein, Brown swiss y Holstein x Brown swiss; y para condición de la pastura, por 120 hectáreas. El consumo se determinó midiendo el área de pasto asignado diariamente a los a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
1
0
3
Order By: Relevance
“…Regarding white clover, the three mowing frequencies (p>0.05) occupy approximately 2/3 of the value indicated by the marked line (30 %) for white clover, probably due to the effect of the time of year and fertilization. Similarly, it has been observed (p<0.05) that weeds tend to decrease as plants mature [11], reaching the lowest level in our study at 60 days, a lower value than that found by Vallejos (2009) [38] and Vallejos (2019) [39], probably due to the effect of shade and competition generated by the height of the plant.…”
Section: Floristic Compositionsupporting
confidence: 79%
See 1 more Smart Citation
“…Regarding white clover, the three mowing frequencies (p>0.05) occupy approximately 2/3 of the value indicated by the marked line (30 %) for white clover, probably due to the effect of the time of year and fertilization. Similarly, it has been observed (p<0.05) that weeds tend to decrease as plants mature [11], reaching the lowest level in our study at 60 days, a lower value than that found by Vallejos (2009) [38] and Vallejos (2019) [39], probably due to the effect of shade and competition generated by the height of the plant.…”
Section: Floristic Compositionsupporting
confidence: 79%
“…Conversely, high mowing frequencies favour ryegrass and make white clover more competitive [37]. Although Vallejos (2009) [38] finds no difference between mowing frequencies about weeds, these can vary between 17.6 and 36.3 % [39]. The objective of this work was to determine the sustainability for production yield, forage biomass, plant height, floristic composition (basically ryegrass, clover and weeds), morphology of ryegrass and white clover in association and nutritive value, at different phenological stages of associated ryegrass-clover pastures in the northern highlands of Peru.…”
Section: Of 12mentioning
confidence: 99%
“…Se puede afirmar que el aumento de frecuencia del pastoreo (de 75 a 40 días), asociado a la renovación de pasturas, fertilización, y a la conservación de forraje para suplementar a las vacas en lactancia, durante el estiaje, es un cambio de manejo que está bien respaldado por el comportamiento productivo y nutricional de las pasturas (Vallejos 2009;Yu Ying y Hou Fu, 2005;Silveira y Kohmann, 2020;Marino y Agnusdei, 2004;Álvarez, 2006;García, 2006;Vallejos, 2017;Vallejos et al, 2019;Carrasco, 2019;Vallejos, 2011) año. Este aumento en los requerimientos de trabajo surge de las labores de encalado (3 jornadas), de la fertilización y siembra (3 jornadas), del corte y acarreo del forraje para conservar (9 jornadas) y del acondicionamiento y empacado del heno de pradera (4,5 jornadas).…”
Section: Evaluación De Las Ventajas Productivas Y Económicas Del Maneunclassified
“…La frecuencia de pastoreo de 70 días a más, influye en la composición botánica de las pastura. En este sentido, el trébol blanco se ve afectado por ser una especie leguminosa rastrera, que ve su crecimiento, reducido debido a la falta de luz solar que la hace fotosintéticamente menos activa (Yu Ying y Hou Fu, 2005), disminuyendo su presencia en las pasturas asociadas reduciéndose a niveles de 1,0 % (Vallejos et al, 2019). De la misma manera, la presencia de especies no deseables (Pennisetum clandestinum, Taraxacum officinale, Rumex cripus)…”
unclassified
See 1 more Smart Citation